2016
DOI: 10.1111/1471-0528.13950
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of congenital syphilis in the United Kingdom: February 2010 to January 2015

Abstract: Objective To estimate the incidence of congenital syphilis in the UK. Design Prospective study. Setting and population United Kingdom. Methods Children born between February 2010 and January 2015 with a suspected diagnosis of congenital syphilis were reported through an active surveillance system. Main outcome measures Number of congenital syphilis cases and incidence. Results For all years, reported incidence was below the WHO threshold for elimination (<0.5/1000 live births). Seventeen cases (12 male, five f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 15 publications
0
14
0
3
Order By: Relevance
“…No syphilis risk factors were identified by their physicians at the time of screening. For two cases, our investigations identified social vulnerabilities that had been highlighted in previous studies [ 3 ]. All four mothers were white and born in the United Kingdom (UK).…”
Section: Case Characteristicsmentioning
confidence: 63%
See 1 more Smart Citation
“…No syphilis risk factors were identified by their physicians at the time of screening. For two cases, our investigations identified social vulnerabilities that had been highlighted in previous studies [ 3 ]. All four mothers were white and born in the United Kingdom (UK).…”
Section: Case Characteristicsmentioning
confidence: 63%
“…Since 2011, the rapid increase in sexually transmitted infectious syphilis (ST-syphilis) (primary, secondary and early latent) diagnoses among gay, bisexual or other men-who-have-sex-with-men (MSM) in England has contrasted with a low, relatively stable number among heterosexuals [ 1 , 2 ]. Congenital syphilis (CS) is rare in England with only 21 cases occurring between February 2011 and January 2017 (data not shown) and [ 3 ]. Cases have been associated with mothers who were socially marginalised and encountered barriers when accessing antenatal care.…”
mentioning
confidence: 99%
“…1,2 Facts such as recent syphilis epidemics were reported around the world, including alarming increases in the infection rates in Brazil, meaning that improved care and the prevention of adverse effects are a substantial necessity. [3][4][5] Syphilis, a sexually transmitted disease (STD) caused by the spirochete Treponema pallidum, goes through distinct phases from the moment of infectionprimary, secondary, latent, and tertiary. During pregnancy, there is no alteration on the physical manifestations of any phase, and transmissibility is possible in any stage of the pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…[26] The study findings of HSM, petechiae, pallor and jaundice were common clinical signs in symptomatic groups of neonates in other study populations. [14,21,27] However, none of our patients had rhinitis or the 'syphilitic snuffles' , which is quoted to affect 4 -22% of neonates and may be the earliest presenting sign. [14,28] Radiological abnormalities, despite being noted in more than half of the neonates who had long-bone X-rays performed, were lower than rates of 75 -100% quoted in the literature.…”
Section: Discussionmentioning
confidence: 86%
“…The influence of social factors on maternal antenatal care has been noted in studies from both the developing and developed world, with incarceration, substance use and prostitution mentioned as possible contributors. [21,22] However, social factors may be more complex and multifaceted; for example, Almeida et al [17] identified married women with a single sexual partner and >8 years of education as having high rates of syphilis.…”
Section: Discussionmentioning
confidence: 99%